Performance of residential property investment returns in an emerging metropolitan area. The awareness, use and gender inequality - Muhammad Saidu Aliero; Salihu Nasiru; Henry Ojobo; Yakubu Aminu Dodo (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2022)
This study assessed the performance of residential property investment returns. To ascertain the awareness, use, and gender inequality in the usage of residential performance data by investors. The paper focuses on risk-return features of the tenement, two and three-bedroom property for investment purposes, in order to improve the understanding of the property market mechanism in Kano metropolis, Nigeria. Unraveling empirically risk-return features of residential property in the metropolitan area is unclear hence the speculative decision on residential investment is widespread. Quantitative research was employed using a questionnaire survey to obtain primary data on annual rental and capital values of residential properties from branch managers of estate firms. This data was afterward transformed into total returns and put to Phillip-Perron unit root test (stationarity). The study utilized both descriptive and inferential statistical techniques for analysis. Findings from the study show that total returns for residential property range from 6.99% to 14.44% with risk-return ranging from 20.92% to 51.54% within the property market, Badawa/GRA property has the lowest risk features hence the most secured location for residential investment, the paper also unveils that gender inequity in the usage of residential property investment performance data is high against women. It is on these findings that the study recommended Badawi/GRA property market for risk-averse investors, persistent sensitization program and incentives (reduction in service charge) targeting women in the property market is encouraged.